2021
DOI: 10.1016/j.ijid.2021.01.017
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiological and radiographical characteristics of asymptomatic infections with the novel coronavirus (COVID-19): A systematic review and meta-analysis

Abstract: The role of asymptomatic infections in the transmission of COVID-19 have drawn considerable attention. Here, we performed a meta-analysis to summarize the epidemiological and radiographical characteristics of asymptomatic infections associated with COVID-19. Methods: Data on the epidemiological and radiographical characteristics of asymptomatic infections were extracted from the existing literature. Pooled proportions with 95% confidence intervals were then calculated using a random effects model. Results: A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 39 publications
4
49
2
Order By: Relevance
“…This was misconstrued across scientific papers and social networks as ASI being responsible for the majority of SARS-CoV-2 infections [ 216 ]. Another unconventional and unnecessary term is “covert infection” [ 217 ], which was used in place of ASI in a systematic review [ 218 ]. Further, in a modeling study, researchers used the term “silent infections” to merge presymptomatic and asymptomatic infections [ 219 ].…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…This was misconstrued across scientific papers and social networks as ASI being responsible for the majority of SARS-CoV-2 infections [ 216 ]. Another unconventional and unnecessary term is “covert infection” [ 217 ], which was used in place of ASI in a systematic review [ 218 ]. Further, in a modeling study, researchers used the term “silent infections” to merge presymptomatic and asymptomatic infections [ 219 ].…”
Section: Main Textmentioning
confidence: 99%
“…Despite the scientific rigor of the articles cited above, generalizability is unclear and the wide prediction intervals of their pooled estimates reflect the considerable methodological and clinical heterogeneity among the studies included. Other systematic reviews with problematic inclusion criteria and definitions published much lower or higher estimates (e.g., 8% [ 218 ], 31% [ 227 ], 39% [ 228 ]) or did not meta-analyze data yet concluded that the proportion of ASI was “at least one third” [ 212 ] or was “not negligible in any population” [ 229 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings highlight that serology is useful to detect previous contact with COVID-19 and could help estimate the extent of asymptomatic spread of the virus (10). Of course, the performances of SARS-CoV-2 serological tests also depend on sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies from China, the United States, and European countries reported that the common symptoms of COVID-19 among pediatric patients were fever, cough, and nausea/vomiting [ 4 ], although most of them were asymptomatic [ 4 , 7 , 8 ]. Additionally, many pediatric patients were infected in their homes [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%